The Role of Strategic Information Systems in Sustainable Development: An Analytical Study in Public Universities in Baghdad - Al-Janabi , Akram Salim H.; Abdulkraeem Ghaleb Al-Mado, Alaa Abdulkraeem Ghaleb Al-Mado (Journal of Economics and Administrative Sciences, 2024)
Purpose: This study aimed to identify the strategic information system and its role and reflections on sustainable development by identifying the level of appreciation and interest of the researched organization in the strategic information system and its dimensions and in sustainable development and its dimensions. Theoretical framework: Recent studies reported good results in university workers and the use of management information systems to improve the requirements of sustainable development and its contexts in universities. Design/methodology/approach: The descriptive analytical approach was adopted for the study in the research community by distributing a questionnaire to a random sample of (86) researchers working in public universities in Baghdad. The research used its scale about the independent variable, the strategic information system, a three-dimensional model that includes individuals, information, and information technology (Laudon & Laudon, 2015), and it also used the sustainable development model that includes the economic, social and environmental dimensions (Yuan & Zuo, 2013). Results: The most important conclusion of the paper is the deep need to pay attention to strategic information systems, their advanced technologies, infrastructure, uses, and cadres by organizations representing the research community to exchange, organize, and manage knowledge constructively and purposefully to develop the requirements and factors of sustainable development and its trends. Research, practical, and social implications: We propose a future research agenda and highlight the cognitive contributions made in higher education in information systems and sustainable development. Originality/value: The results indicate that the number and quality of publications in strategic information systems and sustainable development contribute profoundly to enriching and rooting this trend, in addition to the need to encourage platforms and climates for research and authorship in this vital and relevant field